Mushroom-derived nutraceuticals in the 21st century: an appraisal and future perspectives - Hom-Singli Mayirnao; Karuna Sharma; Pooja Jangir; Surinder Kaur; Rupam Kapoor (Journal of Future Foods, 2025)
Mushrooms are not only delicious additions to various dishes but also possess several health benefits due to their diverse nutritional composition. They are a good source of essential nutrients including protein, vitamins, minerals, and dietary fibre, and are low in fats and calories. Comprehensive studies have been carried out with respect to the nutritive quality of wild and cultivated mushrooms. In recorded history, the purpose of mushroom cultivation was to meet household consumption and gradually, the combination of their nutritional quality and potential health benefits, and the growing interest in functional foods and natural remedies has led researchers to expand their focus towards nutraceutical innovation. The review highlights the utilitarian characteristics of mushrooms gaining popularity as source of nutraceuticals. It summarizes the various factors influencing secondary metabolism. It also identifies knowledge gaps and proposes potential area where more research is needed for optimal use of their potential. Understanding the significance and potential applications of mushrooms can contribute to the development of new products and formulations that can stimulate economic growth and expand the market for mushroom-based nutraceuticals.